2013
DOI: 10.1152/ajpendo.00185.2013
|View full text |Cite
|
Sign up to set email alerts
|

Trehalose prevents neural tube defects by correcting maternal diabetes-suppressed autophagy and neurogenesis

Abstract: isting maternal diabetes increases the risk of neural tube defects (NTDs). The mechanism underlying maternal diabetes-induced NTDs is not totally defined, and its prevention remains a challenge. Autophagy, an intracellular process to degrade dysfunction protein and damaged cellular organelles, regulates cell proliferation, differentiation, and apoptosis. Because autophagy impairment causes NTDs reminiscent of those observed in diabetic pregnancies, we hypothesize that maternal diabetes-induced autophagy impair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
115
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(122 citation statements)
references
References 61 publications
7
115
0
Order By: Relevance
“…Oxidative stress caused by mutations in SOD1 and SOD2 promoter regions, that potentially affect the expression of these two antioxidant enzymes, may be responsible for the formation of human myelomeningocele, a type of NTDs 53 . Oxidative stress mediates the teratogenic effect of hyperglycemia by altering developmental gene expression that is essential for neural tube closure 7, 17 . Recent studies have revealed several important oxidative stress markers in maternal circulation for the early diagnosis of birth defects and other adverse fetal outcomes 51, 54, 55 .…”
Section: Resultsmentioning
confidence: 99%
“…Oxidative stress caused by mutations in SOD1 and SOD2 promoter regions, that potentially affect the expression of these two antioxidant enzymes, may be responsible for the formation of human myelomeningocele, a type of NTDs 53 . Oxidative stress mediates the teratogenic effect of hyperglycemia by altering developmental gene expression that is essential for neural tube closure 7, 17 . Recent studies have revealed several important oxidative stress markers in maternal circulation for the early diagnosis of birth defects and other adverse fetal outcomes 51, 54, 55 .…”
Section: Resultsmentioning
confidence: 99%
“…We also wanted to induce autophagy in a way that would have the lowest probability of toxic effects. For that reason, we decided to use trehalose, a nontoxic disaccharide that has been shown to induce autophagy and to have neuroprotective effects in animal models of Huntington disease, Alzheimer's disease, Parkinson's disease, ALS, and maternal diabetes-associated neural tube defects in the embryo (13,(15)(16)(17)(18)(19)(20). In addition to the positive effects of trehalose in neurodegenerative diseases, there is also evidence that trehalose may have a beneficial effect on impaired endothelial cells in ageing arteries, a risk factor for cardiovascular disease (49).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that neural tube defects are greatly increased in the offspring of women with pregestational diabetes. In a mouse model of maternal diabetes that leads to autophagy impairment in neuroepithelial cells and neural tube defects in the embryo, administration of trehalose in the drinking water prevents these neural tube defects (19,20). Although most studies have examined trehalose in the context of inducing macroautophagy, there is some evidence that it can also induce CMA and counter the effects of the proteasome inhibitor epoxomicin, including elevated reactive oxygen species (ROS), cleaved caspase 3, increased levels of ubiquitinated proteins, and mitochondrial dysfunction and altered morphology (21,22).…”
mentioning
confidence: 99%
“…We have previously demonstrated that apoptosis is implicated in diabetic embryopathy 2, 3, 5, 7, 16 . Our goal is to identify molecular intermediates of the apoptotic cascade responsible for diabetic embryopathy, with ultimately to provide a mechanistic basis for development of therapeutic agents.…”
Section: Clinical Significance and Future Prospectivementioning
confidence: 99%
“…We have used animal models to delineate the mechanism of maternal diabetes-induced malformations 1-5, 7, 8, 16 and specifically focused on the developing neural tube. We have previously demonstrated that apoptosis is implicated in diabetic embryopathy 2, 3, 5, 7, 16 .…”
Section: Clinical Significance and Future Prospectivementioning
confidence: 99%